PERFORMANCE OPTIMIZATION MODEL OF STOCK MUTUAL FUNDS BASED FINANCIAL INFORMATION SYSTEM - Abshor Marantika (Proceeding International Conference on Information Technology and Business, 2015)
The lack of public information on how to invest tobe a major cause of the lack of public interest on capitalmarket investment. Besides of that, for the certaininstrument such as mutual funds of society will getdifficulty in judging and choosing the mutual funds whichbe able to give optimal performance and benefit influencesthe slowness of mutual funds development.Result from this research activity is for finding themeasurement of the performance mutual funds stock byusing stage of stock rotation and stage of stock mutual fundwhich is made to be a accounting management informationsystem and financial. With this stock mutual fundperformance measurement model so that can be tool ofimportant information for investor, society about theinvestment will have good potency of financial and themajor elements causeof the performance of that mutualfunds in capital market. Therefore, society can value andchoose mutual fund which be able to give performance andoptimalization in benefit especially in capital market.Explanatory research, this research has the goal to explainthe relationship between the research variable through thehypotheses based on the data, such as: rotation stage andrisk stage concerning the stock of mutual fund performance.Multiple regression analysis will be used to test the effectof two or more independent variables on the dependentvariable . independent variable in this research is rotationstage and risk stage. Meanwhile in independent variable isthe stock mutual fund performance. The research result forthe simulation of measuring stock of mutual funds model,to measure the stock mutual funds performance.KEY WORDS: performance, mutual funds, stock risk.